Trust and mindreading in adolescents: the moderating role of social value orientation - Derks, Jeffrey; Van Scheppingen, Manon A.; Lee, Nikki C.; Krabbendam, Lydia (Frontiers in Psychology, 2015)
In adolescence, aspects of cognition that are required to deal with complex cooperation situations, such as mentalising and social value orientation, are still in development. In the Trust Game, cooperation may lead to better outcomes for both players, but can also lead to exploitation by the trustee. In the present study, we explore how mindreading, a crucial aspect of mentalising, and social value orientation (whether someone is prosocial or proself) are related to trust. In a group of 217 students (51% girls, Mage = 15.1) social value orientation, mindreading and trust (using the Trust Game) were measured. The result show that social value orientation moderates the relation between mindreading and trust. In the group of prosocials, we find no correlation between mindreading and trust. In the group of proselfs, mindreading is negatively correlated to trust, indicating that proselfs use their mentalising skills to assess that the trustee is likely to exploit them.